Procesowe ujęcie usług logistycznych - Krawczyk, Stanisław (Logistic Services in Process Perspective, 2009)
Scientific analysis of service definitions as used in professional literature shows certain flaws that may negatively affect the evaluation of companies offering logistic services. The confrontation of views presented in foreign publications, especially German, with practical experience suggests that perceiving services in terms of process theory may provide a satisfactory definition of service. This paper briefly presents the most essential aspects of process approach together with resulting modifications in the definition of services. Similarly, consistent modifications are postulated in respect to the definition of logistics services. Perceiving logistics as a function that coordinates development and functioning of support systems for basic company activities, i.e. transcending the traditional perception of logistics as a set of transport, storage and materials flow operations, may prove helpful in proper identification of services that qualify as logistic services. The process perspective offers a more precise delineation of duties and responsibilities of clients and service providers in all phases of the service process as well as emphasizes the role of controlling over the course of logistic services.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 297-305